The spiritual senses perceiving God in Western Christianity - Gavrilyuk, Paul L.; Coakley, Sarah, 1951- (Cambridge, UK ; New York : Cambridge University Press, 2012)
"Is it possible to see, hear, touch, smell and taste God? How do we understand the biblical promise that the 'pure in heart' will 'see God'? Christian thinkers as diverse as Origen of Alexandria, Bonaventure, Jonathan Edwards and Hans Urs von Balthasar have all approached these questions in distinctive ways by appealing to the concept of the 'spiritual senses'. In focusing on the Christian tradition of the 'spiritual senses', this book discusses how these senses relate to the physical senses and the body, and analyzes their relationship to mind, heart, emotions, will, desire and judgement. The contributors illuminate the different ways in which classic Christian authors have treated this topic, and indicate the epistemological and spiritual import of these understandings. The concept of the 'spiritual senses' is thereby importantly recovered for contemporary theological anthropology and philosophy of religion"--
"In this chapter I argue for a reassessment of current academic opinion regarding the theme of the spiritual senses in the writings of Origen of Alexandria (c. 185--c. 254). Specifically, John Dillon has claimed that it is exclusively in Origen's late works that one finds a 'proper' doctrine of the spiritual senses (the crucial features of which will be discussed below).1 Dillon argues that Origen's early works, by contrast, evince only a metaphorical use of the language of sensation.2 The early Origen, according to this reading, is not actually describing the perception of spiritual realities, as is typically thought. Instead, in his early writings Origen uses terms such as 'seeing' and 'hearing' in a figurative manner to describe 'understanding', placing no particular value on the sensory dimension to the terms. In contrast to this assessment, however, I argue here that unexamined aspects of Origen's early writings in fact demonstrate noteworthy continuities between his early and late uses of sensory language. In particular, portions of Origen's early scriptural commentaries and Deprincipiis show that his 'doctrine of the spiritual senses' emerges much earlier than has been recently supposed"--
Machine generated contents note: Introduction Paul Gavrilyuk and Sarah Coakley; 1. Origen of Alexandria Mark J. McInroy; 2. Gregory of Nyssa Sarah Coakley; 3. Augustine Matthew R. Lootens; 4. Gregory the Great George Demacopoulos; 5. Pseudo-Dionysis the Areopagite Paul L. Gavrilyuk; 6. Maximus the Confessor Frederick D. Aquino; 7. Alexander of Hales Boyd Taylor Coolman; 8. Thomas Gallus Boyd Taylor Coolman; 9. Bonaventure Gregory F. LaNave; 10. Thomas Aquinas Richard Cross; 11. Late medieval mystics Bernard McGinn; 12. Nicholas of Cusa Garth Green; 13. Jonathan Edwards and his Puritan predecessors William J. Wainwright; 14. John Wesley Mark T. Mealey; 15. Hars Urs von Balthasar and Karl Rahner Mark J. McInroy; 16. Analytic philosophers of religion William J. Abraham; Bibliography.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Senses and sensation -- Religious aspects -- Christianity; RELIGION / Theology; RELIGION / Christian Theology / General; Electronic books